2019
DOI: 10.20473/j.djmkg.v52.i4.p172-176
|View full text |Cite
|
Sign up to set email alerts
|

The expression of nuclear factor of activated T cell c1 and receptor activator of nuclear factor kappa β induced by Enterococcus faecalis in osteoclastogenesis (laboratory experiment on Wistar rats)

Abstract: Background: Enterococcus faecalis (E. faecalis) is the most common bacteria species in persistent endodontic infection of teeth undergoing root canal treatment at a prevalence of 38%. The virulence factor of this bacterium is Lipoteichoic acid (LTA) which can be recognized by Toll-like receptors-4 (TLR-4) that produce a stimulus and provoke an immune response. Inflammation results in bone defects that feature multiple cytokines and interactions between different cell types. Bone loss within a periapical tooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…18 Several studies mentioned that NFκB is the main inflammatory mediator in rheumatoid arthritis and cancer, cervical cancer, nasopharyngeal carcinoma, periapical lesions and TMJ osteoarthritis. [19][20][21][22][23] Activation of NFκB in the synovial layer also occurred among mice that had synovitis caused by a mechanical stress response due to excessive pressure. 24 NFκB expression was shown to be higher on the 7 th and 14 th days and was at its highest on the 21 st day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Several studies mentioned that NFκB is the main inflammatory mediator in rheumatoid arthritis and cancer, cervical cancer, nasopharyngeal carcinoma, periapical lesions and TMJ osteoarthritis. [19][20][21][22][23] Activation of NFκB in the synovial layer also occurred among mice that had synovitis caused by a mechanical stress response due to excessive pressure. 24 NFκB expression was shown to be higher on the 7 th and 14 th days and was at its highest on the 21 st day.…”
Section: Discussionmentioning
confidence: 99%
“…These results were similar to previous studies that showed that NFκB expression was detected on the 15 th day of observation and played a role in TMJ cartilage damage. 19,21 The occlusal reduction on the right molar in animal groups made premature contact on the collateral side. The occlusal disharmony caused by occlusal reduction induces the excessive stimulation of mechanic sensors at the periodontal ligament and is related to an increase in mastication activities, including in the muscles and the TMJ.…”
Section: Discussionmentioning
confidence: 99%